Photon shielding properties of TiO2 and WO2 incorporated into ordinary concrete: Evaluation for radiotherapy applications (Brazilian Journal of Radiation Sciences, 2025)
This computational study evaluates the photon shielding properties of titanium dioxide (TiO2) and tungsten dioxide (WO2) when incorporated into ordinary concrete. The analysis utilizes the National Institute of Standards and Technology (NIST) XCOM database to calculate mass attenuation coefficients, tenth-value layers (TVL), mean-free paths (MFP), and radiation protection efficiency (RPE) over photon energies ranging from 1 to 10 MeV. Results demonstrate that concrete enhanced with TiO2 and WO2 shows a significant improvement in photon shielding efficiency compared to conventional concrete, particularly at higher photon energy. At 6 MeV, TVL for ordinary concrete is 46% higher than TVL for the sample in which 50% of the gravel was replaced by TiO₂ (by volume), and is 237% higher than the TVL for the sample when considering the incorporation of WO2 in the same proportion. At 10 MeV, these differences change to 42% and 338%, respectively for the samples containing TiO2 and WO2. These findings highlight the superior shielding properties of the TiO2 and WO2 composites, suggesting that they have strong potential for applications in radiotherapy facility rooms and nuclear systems shielding. Experimental validation of these computational results is planned for future work to further confirm their practical applicability.
Keywords: shielding materials; photon attenuation; WO2; TiO2